Using a community-based early childhood development center as a platform to promote production and consumption diversity increases children's dietary intake and reduces stunting in Malawi: A cluster-randomized trial - Gelli, Aulo; Margolies, Amy; Santacroce, Marco; Roschnik, Natalie; Twalibu, Aisha; Katundu, Mangani; Moestue, Helen; Alderman, Harold; Ruel, Marie T. (Elsevier, 2018)
Children in Malawi face nutritional risks related to low-quality diets and chronic malnutrition. This study evaluated the impact of a 1-y early childhood development (ECD) center–based agriculture and nutrition intervention aimed at improving household production diversity, maternal knowledge on child nutrition and feeding practices, and children's diets and anthropometric measures.